Status of varsity, polytechnic applications out on Monday - News Straits, Times (News Straits Times, 2016)
Putrajaya: Sijil Pelajaran Malaysia (SPM) school leavers and their equivalent will be able to check the status of their public university (PU) or premier polytechnic applications tomorrow from noon onwards.